L’équipe come soggetto curante - Realacci, Maria (Il sogno della farfalla, 2018)
The article examines the role the staff has within the context of a community while identifying the compactness and cohesion of the therapeutic staff as the key point for the organization and structuring of the therapeutic process. The author also underlines the need for operators to share the same vision about mental illness and its being manageable and curable. The staff is not to be intended so much as an apparatus of theoretical knowledge and specific education as a group of cohesive and close individuals, who can build a truly therapeutic mental field. To this end, what is needed are human capabilities of relationship, in terms of affective presence and receptiveness, which favours the encounter with patients meant as going towards others with interest.